On Line Teaching Mode of College English based on Smart Classroom in Epidemic Situation - Li, Ou; Li, Xia (2020 International Conference on Big Data and Informatization Education (ICBDIE), 2020)
At present, all kinds of schools at all levels have organized teachers and students to carry out online teaching. How to achieve "substantial equivalence" of online teaching has become an urgent problem. Based on the theory of constructivism, this paper compares the advantages and disadvantages of rain classroom and u campus intelligent teaching platform, and explores the online teaching mode of College English. After several weeks of exploration, through the analysis of questionnaire, it is verified that the model has been recognized by most students.